2009
DOI: 10.1186/1471-2121-10-22
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interaction between Actinin-Associated LIM Protein (ALP) and the rod domain of α-actinin

Abstract: Background: The PDZ-LIM proteins are a family of signalling adaptors that interact with the actin cross-linking protein, α-actinin, via their PDZ domains or via internal regions between the PDZ and LIM domains. Three of the PDZ-LIM proteins have a conserved 26-residue ZM motif in the internal region, but the structure of the internal region is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…This is in agreement with the observation that 2 min noradrenaline stimulation induced the phosphorylation of ERM, which is required for its binding to EBP50 (68). Among these proteins, ␣-actinin has already been detected as an interacting partner of PDZ domain containing proteins (10,28,36,74). The identification by mass spectrometry of the proteins interacting with EBP50 in noradrenaline-stimulated arteries revealed that almost all the EBP50 interacting partners were related to the cytoskeleton.…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with the observation that 2 min noradrenaline stimulation induced the phosphorylation of ERM, which is required for its binding to EBP50 (68). Among these proteins, ␣-actinin has already been detected as an interacting partner of PDZ domain containing proteins (10,28,36,74). The identification by mass spectrometry of the proteins interacting with EBP50 in noradrenaline-stimulated arteries revealed that almost all the EBP50 interacting partners were related to the cytoskeleton.…”
Section: Discussionsupporting
confidence: 89%
“…As expected, Zasp52 binds better to α-actinin than to actin. The dissociation constant is very similar to that of human ALP binding to α-actinin [33,34].…”
Section: Plos Onementioning
confidence: 56%
“…However, only for ALP, RIL, CLP36, and ZASP/Cypher, the PDZ domain was confirmed to interact directly with α-actinin [7, 28, 3941]. To further complicate the issue, the ZM region of ALP has been shown to bind directly to α-actinin [28, 42] and the ZM region, as well as the LIM domains of ZASP/Cypher colocalize with α-actinin [7, 29]. Moreover, LIM domains of CRP proteins can bind α-actinin [43, 44].…”
Section: Discussionmentioning
confidence: 99%